PELATIHAN CREATIVEPRENEURSHIP SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN MANAJEMEN USAHA BATIK LASEM KABUPATEN REMBANG - Muhammad Tahwin; Dian Ayu Liana Dewi; Fajar sodiq; Ahmad Nasuha; Indah Wahyuni (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2024)
In this community service activity as a partner is Batik Tulis Asri Anna Budaya. Batik Tulis Lasem Asri Anna Budaya is one of UMKM in Rembang Regency that produces Batik Tulis Lasem. The results of interviews by the YPPI Rembang University Service Team with partners obtained data that in managing their business they had not carried out administration well. Beside that, partners also have not utilized information technology in marketing. This is due to limited knowledge about the benefits of information technology for product marketing. The agreed solution as a form of service activity is business management training (creativepreneurship): training in motivation, creativity and innovation, administration and e-marketing. The aim of service activities is to improve partners' business management capabilities so that they can develop creativity and innovation in running the business. Activities are carried out in three stages, namely preparation, implementation and evaluation. The results of the activities that were successfully achieved were that partners' motivation to develop their business increased along with the growth of creativity and innovation in developing their products. Partners have also begun to realize the importance of e-marketing in increasing their sales. Keywords: creativepreneurship, improving, business management